Estruturas secretoras florais e extraflorais em espécies de Gongora Ruiz & Pav., Stanhopea Frost ex Hook. e Coryanthes Hook. (Orchidaceae: Stanhopeinae) ocorrentes na região Amazônica - (:unkn) unknown (Museu Paraense Emilio Goeldi, 2015)
Orchidaceae, is one of the largest families of angiosperms, are widely known for the diversity of shapes and colors of their flowers. Features that attract pollinators potentials and gives them a relationship, often specific with the insects. The respective genus under study, Gongora Ruiz & Pav., Stanhopea Frost ex Hook. and Coryanthes Hook., belong the subtribe Stanhopeinae Benth., which consists of approximately 257 species belonging to 20 genera, are neotropical distribution orchid and exclusively pollinated by bees Euglossini male. At the present moment, the anatomical studies of secretory structures in Stanhopeinae, described the structures that produce lipids, as elaiophores and osmophores. And in order to expand and contribute to the anatomical knowledge of Stanhopeinae group, this study aimed to investigate the secretory structures in species of Gongora Ruiz & Pav., Stanhopea Frost ex Hook., and Coryanthes Hook., orchids, that occurring in the Amazon region. The flowers were collected for the analysis usual anatômics and reserved samples for subsequent incorporation into the herbarium MG. The Stanhopeinae analyzed, offer rewards produced by osmophores elaiophores and their pollinators, bees Euglossini males, while floral and extrafloral Nectarios produce nectar for the ants, which help protect the plants and flowers from potential invasive plants and herbivores imminent.
Keywords: Gongora Ruiz & Pav.; Stanhopea Frost ex Hook.; Coryanthes Hook.; Orquídeas; Estruturas secretoras; Euglossini; Polização; Osmóforos; Elaióforos; Nectários; Região Amazônica; CNPQ::CIENCIAS BIOLOGICAS::BOTANICA